The influence of land consolidation works on the efficiency of the production process - Jacek Gniadek; Jarosław Janus; Stanisław Bacior (Acta Scientiarum Polonorum. Formatio Circumiectus)
The study will present studies involving the assessment of changes in shape of plots caused by carrying out land consolidation in Koźlice in Dolnośląskie Voivodeship. The research material includes all the land in the studied village. The source of data for the assessment will be the digital registry map in the state before and after the land consolidation. During the processing of the output data and determination of the necessary technical parameters for the tested surface elements, informatics and statistical tools will be implemented. The basic element of research, allowing the comparison of the land consolidation process efficiency will be registry plots and their continuous parts, under one form of use (arable land). The detailed research will concern the assessment of the shape of arable plots and their distribution in the village area. For each of them the shape index in the form of the cost of cultivation depending on their layout will be specified. The obtained result of the research will allow the determination, the extent to which the land consolidation carried out in the village Koźlice improved the conditions of agricultural production space.